Snakebites in Mostar region, Bosnia and Herzegovina - Curić, Ivo, liječnik (Array, 2009)
Summary: The aim of this study was to provide an overview of the snakebites in patients hospitalized at the Mostar Clinical Hospital, admitted between 1983 and 2006. A total of 341 patients were recorded, with moderate men predominance (52.8%). Majority of patients were bitten for the first time (99.1%). In 98.8% of patients snakebite occurred to the bare skin, most commonly during June to September period (64.2%). Snakebites were the commonest in agricultural workers (48.1%). Until 2003 all admitted patients were treated according to Russel’s scheme (3-anti). As of 2003 new treatment scheme was applied, resulting in the reduction of antidote and supportive treatment use, causing a reduction in the number of clinically apparent allergic reactions. Serum sickness was recorded in only 2 patients, while lethal outcome was recorded in one (0.3%). Overall results indicate that lethality of snakebite is low, and that patients were often administered treatment without medical indication. High number of tourists as well as the presence of the peace keeping troops and other visiting personnel in this region make the snakebites and awareness on snakes not only a local issue, but also more general concern